Anxiety but Not Menopausal Status Influences the Risk of Long-Covid-19 Syndrome in Women Living in Latin America - Lopez-Pizarro, M (ELSEVIER IRELAND LTD, 2024)
Objective: To study sociodemographic and clinical factors associated with the long-COVID-19 syndrome among women living in Latin American countries using undirected and directed methods. Method: We studied 347 patients with COVID-19 (confirmed by polymerase chain reaction) living in nine Latin American countries between May 2021 and July 2022, including 70 premenopausal, 48 perimenopausal, and 229 postmenopausal women. We compared the sociodemographic and general health information of women with (n = 164) and without (n = 183) the long-COVID-19 syndrome. They also completed the Connor-Davidson Resilience Scale, the Fear of COVID-19 Scale, the Jenkins Sleep Scale, and the Menopause Rating Scale to define the minimum set of variables for adjustment. We designed a directed acyclic graph (DAG) to identify factors related to the long-COVID-19 syndrome. Data were submitted to categorical logistic regression analyses. Results are reported as means and standard deviations or beta-coefficients and 95 % confidence intervals. Results: Women with long-COVID-19 syndrome had a poor lifestyle, severe menopause symptoms, hypertension, insomnia, depression, anxiety, chronic diseases/conditions, risk of hospitalization, sleep disturbance, and low menopause-related quality of life compared to women without the syndrome. The DAG identified the following long-COVID-19 covariates: age, obesity, anxiety, depression, cancer, lifestyle, smoking, and menstrual status. A multivariable logistic model with these covariates indicated that anxiety is the only factor to be significantly associated with long-COVID-19 syndrome, whereas other covariates were confounding factors. There was no significant influence of menopausal status on the long-COVID-19 syndrome. Conclusion: Among factors selected by the DAG, only anxiety was significantly associated with the long-COVID-19. There was no significant influence of the menopause status on the long-COVID-19 syndrome in the studied population.